The Ubiquitin Ligase Ubr11 Is Essential for Oligopeptide Utilization in the Fission Yeast Schizosaccharomyces pombe - Kitamura, Kenji (American Society for Microbiology, 2012)
Uptake of extracellular oligopeptides in yeast is mediated mainly by specific transporters of the peptide transporter (PTR) and oligopeptide transporter (OPT) families. Here, we investigated the role of potential peptide transporters in the yeast Schizosaccharomyces pombe. Utilization of naturally occurring dipeptides required only Ptr2/SPBC13A2.04c and none of the other 3 OPT proteins (Isp4, Pgt1, and Opt3), whereas only Isp4 was indispensable for tetrapeptide utilization. Both Ptr2 and Isp4 localized to the cell surface, but under rich nutrient conditions Isp4 localized in the Golgi apparatus through the function of the ubiquitin ligase Pub1. Furthermore, the ubiquitin ligase Ubr11 played a significant role in oligopeptide utilization. The mRNA levels of both the ptr2 and isp4 genes were significantly reduced in ubr11Δ cells, and the dipeptide utilization defect in the ubr11Δ mutant was rescued by the forced expression of Ptr2. Consistent with its role in transcriptional regulation of peptide transporter genes, the Ubr11 protein was accumulated in the nucleus. Unlike the situation in Saccharomyces cerevisiae, the oligopeptide utilization defect in the S. pombe ubr11Δ mutant was not rescued by inactivation of the Tup11/12 transcriptional corepressors, suggesting that the requirement for the Ubr ubiquitin ligase in the upregulation of peptide transporter mRNA levels is conserved in both yeasts; however, the actual mechanism underlying the control appears to be different. We also found that the peptidomimetic proteasome inhibitor MG132 was still operative in a strain lacking all known PTR and OPT peptide transporters. Therefore, irrespective of its peptide-like structure, MG132 is carried into cells independently of the representative peptide transporters.